Real-world data of azacitidine for relapsed/refractory nodal T-follicular helper cell lymphoma in 11 patients - Faustmann, Philipp; Schroeder, Jan C.; Riedel, Andreas; Schürch, Christian M.; Killinger, Simon; Phely, Laurent; Mix, Lucas; Lengerke, Claudia; Häring, Max-Felix (Frontiers in Hematology, 2025)
Relapsed or refractory (r/r) nodal T-follicular helper cell lymphoma of the angioimmunoblastic type is a rare disease with a dismal prognosis. This disease usually harbors mutations in epigenetic modifiers. A standard of treatment for an r/r disease is not known. Here, we report real-world data of 11 patients with a median age of 73 years, treated with azacitidine, a hypomethylating agent. Overall survival was 182 days. Five patients died from progressive disease; three were in complete remission after allogeneic stem cell transplantation; two were in complete remission, still receiving azacytidine; and one was under treatment for relapse. The treatment was well-tolerated despite the advanced age, and there was a high burden of comorbidities with a median hematopoietic cell transplantation-specific comorbidity index (HCT-CI) of 5, a score for identifying relevant comorbidities. However, a grade 3 or 4 hematological toxicity occurred in nine patients. Azacitidine may be a suitable treatment option for some patients with r/r nodal T-follicular helper cell lymphoma.